Florida's Citrus Canker Eradication Program (CCEP): Summary of Annual Costs and Benefits - Marisa L. Zansler; Thomas H. Spreen; Ronald P. Muraro (EDIS)
In the analysis presented in this paper, the benefits of the Citrus Canker Eradication Program (CCEP) are estimated through an analysis of the Florida citrus industry under the scenario that citrus canker has become established. All other factors are held constant. The estimated net change in revenue in the fresh and processed markets and the additional costs of production were measurements of the predicted benefits. This is EDIS document FE532, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published March 2005.